New acanthodriline earthworms from México (Oligochaeta: Megascolecidae) - James, Samuel W. (Instituto de Ecología, A.C., 1993)
Five new species and two new genera of earthworms are described from several locations in Southern and eastern México. These species are all acanthodriline Megascolecidae without nephridial vesicles or calciferous glands. The new genus Protozapotecia has two díscrete gízzards in segments separated by a muscular septum, just as in the closely related Zapotecia with three gízzards. The new genus Larsonidrilus has doubled próstatas or próstata homologs and muscular sucker-shaped genital markings.